A Magical Match - Higginson, Sheila Sweeny 1966-; Character Building Studio (Firm); Disney Storybook Artists (Los Angeles ; Disney Press, 2014)
When Sofia meets her friend Lucinda's adorable pet rabbit, Hexie, she's sure that Hexie and Clover will become fast friends. But Clover is all about eating and barely notices Hexie. The little witch thinks she has a magic solution, but this match may not be so magical after all!
At head of title: Disney Sofia the First.
"Includes over 60 stickers!"
Keywords: Princesses -- Juvenile fiction; Witches -- Juvenile fiction; Rabbits -- Juvenile fiction; Magic -- Juvenile fiction; Toy and movable books -- Specimens; Magic; Princesses; Rabbits; Witches; Fiction; Juvenile works